Return to work and productivity loss after surgery: A health economic evaluation. (November 2021) - Hah, Jennifer M.; Lee, Evelyn; Shrestha, Rupendra; Pirrotta, Luke; Huddleston, James; Goodman, Stuart; Amanatullah, Derek F.; Dirbas, Frederick M.; Carroll, Ian R.; Schofield, Deborah
Abstract: Background: We aimed to identify preoperative psychosocial factors associated with return-to-work (RTW) and the associated cost of productivity loss due to work absenteeism following surgery. Research demonstrates a high economic burden from productivity loss after surgery, but the comparative cost of productivity loss relative to income across different operations has not been examined. Materials and methods: A mixed surgical cohort recruited for a randomized controlled trial were prospectively followed for up to two years following surgery with daily phone assessments to three months, weekly assessments thereafter to six months, then monthly assessments thereafter to determine RTW status, opioid use and pain. Results: 183 of 207 (88.3%) patients in paid employment prior to surgery, who provided at least one day of follow-up, were included in this analysis. The average cost of productivity loss due to work absenteeism was $13 761 (median $9064). Patients who underwent total knee replacement incurred the highest income loss. Medical claims filed before surgery were significantly associated with relative income loss (AOR 5.09; 95% CI 1.73–14.96; p < 0.01) and delayed postoperative RTW. Elevated preoperative PTSD symptoms were associated with delayed RTW (HR 0.78; 95%CI 0.63–0.96; p-value = 0.02) while male gender (HR 1.63; 95%CI 1.11–2.38; p-value = 0.01) was associated with faster postoperative RTW. Conclusion: Surgery places a high economic burden on individuals due to postoperative productivity loss. Multidisciplinary approaches, such as pathways, that facilitate the operation and recovery may mitigate the economic consequences for patients, employers, and the healthcare system. Highlights: Postoperative return to work (RTW) improves mental health and quality of life. We compared the cost of productivity loss relative to income across operations. The average cost of productivity loss due to work absenteeism was $13, 761. Total knee replacement incurred the highest income loss across operations. Preoperative medical claims and PTSD symptoms were associated with delayed RTW.